Bidding behaviors of GENCOs under bounded rationality with renewable energy. (1st July 2022) - Guo, Hongye; Chen, Qixin; Shahidehpour, Mohammad; Xia, Qing; Kang, Chongqing
Abstract: With the worldwide restructuring of power markets, it is more meaningful to analyze the bidding behaviors of generation companies (GENCOs). A realistic bidding behavior model can help to design better power market mechanisms. However, most existing studies usually use strong assumptions, where all GENCOs behave perfectly rationally when participating in power markets. Many GENCOs' observed bidding behaviors are proved to deviate from the simulated perfectly rational ones. Thus, it is significant to introduce individual subjective perspectives into the bidding behavior modeling to obtain more realistic models. Although several studies have been working on this topic by introducing bounded rationality, they still have some problems in modeling bounded rationality, power system operation, power market rules, etc. This paper proposes a novel bidding behavior model for GENCOs under bounded rationality with renewable energy to overcome these problems. The introduced bounded rationality features include prospect theory in the form of framing effects and the concept of fairness constraints on profit-making. A Stackelberg game model is formulated to analyze the interaction between a GENCO with renewables and a day-ahead power market. The proposed model is nonlinear, which is further transformed into a mixed-integer linear formulation by applying Karush–Kuhn–Tucker theorem and strong duality theorem. Based on a modified IEEE-30 bus system with high renewable, an illustrative example is proposed to demonstrate the effectiveness of the proposed model and analyze the bidding behaviors of bounded rational GENCOs and the corresponding effects on power markets. Highlights: A model to simulate bidding behaviors of GENCOs under bounded rationality is built. Three bounded rationality features are integrated into the bidding model. The nonlinear Stackelberg game model is linearized by applying a solution method. Bidding behaviors of GENCOs with renewables under bounded rationality are analyzed.